Real-time computation of diffraction fields for pixelated spatial light modulators - (:unkn) unknown (OPTICAL SOC AMER, 2015)
Fast calculation of diffraction field from a three-dimensional object is an important problem in holographic three-dimensional television. As a result of this, several fast algorithms can be found in the literature, but most them omit pixelated structure of the display device used in the reconstruction process. We propose a fast algorithm for diffraction field calculation from a three-dimensional object for a pixelated display device. Real-time calculations can also be achieved when the proposed algorithm is run on a graphical processing unit. Performance assessment of the algorithm is obtained by the computation time of the diffraction field and the error on the reconstructed object. The proposed algorithm employs a precomputed look-up-table which is formed by one-dimensional kernels. Each kernel in the look-up-table denotes a diffraction field on the display device from a point light source at a specific depth along longitudinal axis. Allocated memory space by the precomputed look-up-table is optimized according to the sampling policy of the depth parameter. Look-up-table formed by uniformly sampled depth parameter provides the same error on the reconstructed object with less number of kernels. Also, optical experiments are conducted and successful results are obtained. (C) 2015 Optical Society of America
Keywords: COMPUTER-GENERATED HOLOGRAMS; LOOK-UP TABLE; 3-DIMENSIONAL SURFACE OBJECTS; FRESNEL DIFFRACTION; TILTED PLANES; RECONSTRUCTION; PROPAGATION; ALGORITHM; TRANSFORM